Legal environment for technology transfer in Taiwan - LIU, Kung-chung (Institutional Knowledge at Singapore Management University, 2002)
In an effort to become an industrialized country, Taiwan, the Republic of China (ROC) has relied heavily on technology transfers and investment from abroad. The Taiwanese government adopted a heavy-handed policy of regulating investments made by foreigners and overseas Chinese in 1954. These policies include the Foreigner Investment Act (FIA) and the Overseas Chinese Investment Act (OCIA), which require all foreigners and overseas Chinese to obtain the Ministry of Economic Affairs (MOEA) approval prior to making any investments.1 Such investments may also be in the form of patents, trademarks, copyright, know-how, and other intellectual property (IP).2 In 1962, the Technology Cooperation Law (TCL) was enacted to regulate those investments that provided patents and know-how in return for royalties instead of capital stock.3 The TCL marked the commencement of an era in which state-directed intervention was used to control the direction and results of technology transfer from a strategic viewpoint of national development and the optimal use of scarce foreign exchange reserves. The TCL was complemented with a network of laws providing a variety of incen